Prevalence of Gastrointestinal Pathogens Detected by Multiplex Polymerase Chain Reaction in a Prospective Cohort of Men Who Have Sex With Men Taking Human Immunodeficiency Virus Preexposure Prophylaxis—New York City, 2019–2020. (3rd August 2021) - Purpura, Lawrence; Zucker, Jason; LaSota, Elijah; Lopez, Mabel; Spicehandler, Rebecca; Carnevale, Caroline; Perez, Edward; Richards, Paul; Chang, Jennifer; Cohall, Al; Uhlemann, Anne-Catrin; Whittier, Susan; et al.
Abstract: Multiplex polymerase chain reaction testing for gastrointestinal pathogens was performed on a longitudinal cohort of 110 men who have sex with men taking human immunodeficiency virus preexposure prophylaxis. At least 1 pathogen was detected among 50 (45%) participants, with some participants testing positive for the same pathogen on multiple consecutive visits over a period of months.